Vitamin D Deficiency is Associated with Hypocalcemia in Preterm Infants - Nabiel, Nabiel; Nugroho, Hari Wahyu; Moelyo, Annang Giri (Cell and BioPharmaceutical Institute, 2024)
Background: Vitamin D deficiency results in various problems, like rickets, osteomalacia, heart problems, cancer, diabetes, and autoimmune diseases. Hypocalcemia is a common disorder among preterm infants, indicating vitamin D deficiency. This study was conducted to analyze the association of vitamin D deficiency with hypocalcemia in preterm infants.Materials and methods: A cross-sectional study was performed in preterm infants born in our hospital from December 2022 to May 2023. Venous blood was collected within the first 24 hours to assess vitamin D and calcium levels. Chi-square test and logistic regression analysis were used to assess the association of gestational age, sex, birth weight, and vitamin D with the incidence of hypocalcemia. The significance was determined with p<0.05.Results: There were 40 preterm newborns, comprising 37.5% moderately preterm, 20% very preterm, and 42.5% extremely preterm. Most subjects were female (52.5%). Low birth weight, very low birth weight, and extremely low birth weight occurred in 55%, 27.5%, and 17.5%, respectively. Vitamin D insufficiency and deficiency were observed in 20% and 80% subjects, respectively. Most subjects had hypocalcemia (62.5%). Chi-square test obtained a significant association of vitamin D deficiency with hypocalcemia (p=0.029).Conclusion: Vitamin D deficiency is significantly associated with the incidence of hypocalcemia in preterm infants.Keywords: Vitamin D, hypocalcemia, preterm neonates